Sensibilisation et réponse des agriculteurs du nord-est de la Thaïlande à la pollution environnementale aux pesticides - Bernard Formoso (VertigO, 2021)
To meet the needs of agricultural intensification, on which their standard of living depends, Thai smallholder farmers are increasingly using pesticides. From a quantitative and qualitative survey carried out in August 2019 among 100 farmers from two villages in Khon Kaen province, and from the results of large-scale blood testing by the Thailand’s public health department, the author highlights the impact of pesticides on the health of petty farmers, as well as their perception of the health and environmental dangers to which the massive use of pesticides exposes them. The article also examines farmers' varied responses to government incentives for ecological transition. Finally, it reviews the responses that they provide to these incentives, depending on the regime of constraints to which they are subject, in a context of repeated climatic accidents with a strong impact on yields and very significant fluctuations in world prices of cash crops.pesticides, Thailand, agriculture